The nucleation-controlled intermetallic grain refinement of Cu-Sn solid-liquid interdiffusion wafer bonding joints induced by addition of Ni particles. (November 2018) - Li, Z.L.; Tian, H.; Dong, H.J.; Guo, X.J.; Song, X.G.; Zhao, H.Y.; Feng, J.C.
Abstract: In this study, Ni particle was validated as an effective grain refiner for the Cu-Sn solid-liquid interdiffusion (SLID) wafer bonding joints, which induced a dispersive non-interfacial nucleation of intermetallic grains, effectively preventing the grain mergence phenomenon. With increasing the Ni particle addition, there were significant reductions in both the (Cu, Ni)6 Sn5 grain size and the Cu3 Sn layer thickness, 6 wt% addition of Ni particles even led a formation of the intermetallic joints only consisted of (Cu, Ni)6 Sn5 grains with an average grain size of 1.3 μm. (Cu, Ni)6 Sn5 grain refinement could notably enhanced the shear strength of the intermetallic joints. Graphical abstract: Unlabelled Image